Mind the gaps in research on the control of gastrointestinal nematodes of farmed ruminants and pigs. (10th November 2017) - Charlier, J.; Thamsborg, S. M.; Bartley, D. J.; Skuce, P. J.; Kenyon, F.; Geurden, T.; Hoste, H.; Williams, A. R.; Sotiraki, S.; Höglund, J.; Chartier, C.; Geldhof, P.; et al.
Abstract : Summary: Gastrointestinal (GI) nematode control has an important role to play in increasing livestock production from a limited natural resource base and to improve animal health and welfare. In this synthetic review, we identify key research priorities for GI nematode control in farmed ruminants and pigs, to support the development of roadmaps and strategic research agendas by governments, industry and policymakers. These priorities were derived from the DISCONTOOLS gap analysis for nematodes and follow‐up discussions within the recently formed Livestock Helminth Research Alliance (LiHRA). In the face of ongoing spread of anthelmintic resistance (AR), we are increasingly faced with a failure of existing control methods against GI nematodes. Effective vaccines against GI nematodes are generally not available, and anthelmintic treatment will therefore remain a cornerstone for their effective control. At the same time, consumers and producers are increasingly concerned with environmental issues associated with chemical parasite control. To address current challenges in GI nematode control, it is crucial to deepen our insights into diverse aspects of epidemiology, AR, host immune mechanisms and the socio‐psychological aspects of nematode control. This will enhance the development, and subsequent uptake, of the new diagnostics, vaccines, pharma‐/nutraceuticals, control methods and decision support tools required to respond to the spread of AR and the shifting epidemiology of GI nematodes in response to climatic, land‐use and farm husbandry changes. More emphasis needs to be placed on the upfront evaluation of the economic value of these innovations as well as the socio‐psychological aspects to prioritize research and facilitate uptake of innovations in practice. Finally, targeted regulatory guidance is needed to create an innovation‐supportive environment for industries and to accelerate the access to market of new control tools.